Answer:
The equation that passes through (−7,−3)and (−2,−1) is y=2/5x-1/5
Step-by-step explanation:
m=y²-y¹/x²-x¹
m=(-1)-(-3)/(-2)-(-7)
m=2/5
y-y=m(x-x¹)
y-(-1)=2/5(x-(-2)
y+1=2/5x+4/5
-1 -1
y=2/5x-1/5
Answer:
- 8x^3+1 ⇒ (2x+1)(4x^2−2x+1)
- 2x^4+16x ⇒ 2x(x+2)(x^2−2x+4)
- x^3+8 ⇒ (x+2)(x^2−2x+4)
Step-by-step explanation:
The factoring of the sum of cubes is ...
a³ +b³ = (a +b)(a² -ab +b²)
1. a=2x, b=1
= (2x)³ + 1³
__
2. There is an overall factor of 2x. Once that is factored out, a=x, b=2.
= (2x)(x³ +2³)
__
3. a=x, b=2
= x³ +2³
B x is equal to 3
hope this helps
Step-by-step explanation:
h2 - g
Putting values
(4)2 - 32
8 - 32
= - 24